Água de reúso em rabanete (Raphanus sativus L.): implicações agronômicas e sanitárias - Mendes, Paulo Eduardo Ferreira (2014)
Due to increasingly irrigation water source scarcity, treated wastewater (TWW) is becoming a more attractive by nutrients source, showing sanitary and agronomics feasibility. In this way, this research evaluated, in a greenhouse conditions influence of superficial drip irrigation on radish (Raphanus sativus L.) cv. Crimson Giant production and nutritional status, as well as, soil chemical attributes changes; and, soil and radish sanitary contamination risk submitted to two water sources. The experiment was carried out at CCA/UFSCar, Araras, SP and a completely randomized design was adopted, with two treatments [AB- potable water (PW) and AR- treated wastewater (TWW)]. Soil and radish sample were submitted to sanitary analyses. The results showed that drip TWW didn t commit radish nutritional, production and increased macronutrients availability. However, soil sodium adsortion ratio (SAR) and exchangeable sodium percentage (ESP) increased by TWW application, but without salinization and sodification risk. Furthermore, radish showed out of sanitary conditions, indicated by the E. coli and total coliformis contamination, impossible its commercialization and in natura consumption. Considering the obtained results, suggest take appropriate action to improve the TWW treatment efficiency and promote radish sanitary conditions. The obtained results demonstrated the wastewater reuse feasibility as a source of nutrients to radish, substituting or reducing the application of commercial fertilizers and reducing the cost production.